Effect of additional food waste slurry generated by mesophilic acidogenic fermentation on nutrient removal and sludge properties during wastewater treatment. (December 2019) - Tang, Jialing; Pu, Yunhui; Wang, Xiaochang C.; Hu, Yisong; Huang, Jin; Ngo, Huu Hao; Pan, Shengwang; Li, Yuyou; Zhu, Nengmin
Graphical abstract: Highlights: Nutrients removal was enhanced using FSFW produced under mesophilic temperature. Complete nitrogen removal could be achieved at the C/N ratio of 8 with FSFW. Organic acid and solid organics are easily- and slowly-biodegradable, respectively. Sludge dewaterability and settleability were improved after adding the FSFW. Microbial community structures were selectively enriched. Abstract: Fermentation slurry from food waste (FSFW) generated by acidogenic fermentation at mesophilic temperature was utilized to improve the nutrients removal from wastewater. Organic acids (such as lactate and volatile fatty acids) in the FSFW behaved as readily biodegradable carbon sources, while the particulate and macromolecular organics acted as slowly biodegradable carbon sources during denitrification processes. The FSFW dosage significantly influenced the nitrogen removal performance, and a C/N ratio (in terms of chemical oxygen demand to nitrogen ratio) of 8 could achieve complete denitrification in the batch tests. In a sequencing batch reactor (SBR) using FSFW for long-term wastewater treatment, extracellular polymeric substances (EPS) gradually accumulated, sludge particle size significantly increased, and microbial communities were selectively enriched, which contributed to promoting the nitrogen (>80%) and phosphate (90.1%) removal efficiencies. Overall, the FSFW produced by acidogenic fermentation under mesophilic temperature served as an excellent intermediary between FW valorization and wastewater treatment.